The Influence of Calcium and Iron Supplementation in Pregnant Women to Affect Newborn Body Length in Bengkulu - Agung Riyadi; Lisma Ningsih; Jumiyati Jumiyati; Antun Rahmadi (Universitas Airlangga, 2023)
In 2021, the rate of stunting in Indonesia was 24.4%, and 21.1% happened in Bengkulu province. In 2020, the proportion of pregnant women who receive iron tablets in Bengkulu Province was 97%. Some regencies have a lower proportion, such as North Bengkulu at 87%. Pregnant women who suffer from the lack of iron and folic acid intake may experience anemia and impaired fetal growth. The aim of this study is to investigate the effect of calcium and iron supplementation in pregnant women on newborn body length in Bengkulu Province. This study used an experimental design with a post-test-only control group. The population was third semester pregnant women in Bengkulu Province. Subjects were taken using purposive sampling technique. The number of subjects involved was 29 in intervention group and control group. Instruments used ini this study were food frequency questionaire (FFQ), mid upper arm circumference tape, and a respondent characteristics questionnaire. Data analysis methods include independent t-test, correlation, and double linear regression. The consumption of iron tablets and calcium tablets (p=0.0001), as well as the nutritional status of pregnant women (p=0.0001), have significant effect on newborns body length. Calcium and iron tablets supplementation improve the nutritional status of pregnant women and increase newborn body length. However, it should be measured by using same controlling variables such as education, age, parity, protein intake, vitamin C intake, knowledge and gestational age of childbirth.